2016
DOI: 10.18632/oncotarget.14206
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Nectin-4 on the surface of ovarian cancer cells alters their ability to adhere, migrate, aggregate, and proliferate

Abstract: The cell adhesion molecule Nectin-4 is overexpressed in epithelial cancers, including ovarian cancer. The objective of this study was to determine the biological significance of Nectin-4 in the adhesion, aggregation, migration, and proliferation of ovarian cancer cells. Nectin-4 and its binding partner Nectin-1 were detected in patients’ primary tumors, omental metastases, and ascites cells. The human cell lines NIH:OVCAR5 and CAOV3 were genetically modified to alter Nectin-4 expression. Cells that overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…AKT can be activated by treatment with LPA (58) and by ascites (59), and patients with AKT2 alterations have a poor prognosis (60). AKT promotes EMT (61), which corroborates our recent work in which Nectin-4 knockdown cells had increased expression of mesenchymal markers such as vimentin and decreased expression of epithelial markers such as E-cadherin (15).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…AKT can be activated by treatment with LPA (58) and by ascites (59), and patients with AKT2 alterations have a poor prognosis (60). AKT promotes EMT (61), which corroborates our recent work in which Nectin-4 knockdown cells had increased expression of mesenchymal markers such as vimentin and decreased expression of epithelial markers such as E-cadherin (15).…”
Section: Discussionsupporting
confidence: 86%
“…Ovarian cancer cells exist both as free-floating single cells and as aggregated spheroids in ascites fluid, and our recent study showed that Nectin-4 is essential for the formation of compact spheroids (Fig. 7d) (15). We have previously published that spheroids adhere to mesothelial cells (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations